Linking Electronic Relaxation Dynamics and Ionic Photofragmentation Patterns for the Deprotonated UV Filter Benzophenone-4 - Wong, Natalie G. K. (J Phys Chem Lett, 2021)
[Image: see text] Understanding how deprotonation impacts the photophysics of UV filters is critical to better characterize how they behave in key alkaline environments including surface waters and coral reefs. Using anion photodissociation spectroscopy, we have measured the intrinsic absorption electronic spectroscopy (400–214 nm) and numerous accompanying ionic photofragmentation pathways of the benzophenone-4 anion ([BP4–H](−)). Relative ion yield plots reveal the locations of the bright S(1) and S(3) excited states. For the first time for an ionic UV filter, ab initio potential energy surfaces are presented to provide new insight into how the photofragment identity maps the relaxation pathways. These calculations reveal that [BP4–H](−) undergoes excited-state decay consistent with a statistical fragmentation process where the anion breaks down on the ground state after nonradiative relaxation. The broader relevance of the results in providing a basis for interpreting the relaxation dynamics of a wide range of gas-phase ionic systems is discussed.